2018
DOI: 10.1080/15563650.2018.1457792
|View full text |Cite
|
Sign up to set email alerts
|

Trends in intentional abuse or misuse of benzodiazepines and opioid analgesics and the associated mortality reported to poison centers across the United States from 2000 to 2014

Abstract: Intentional abuse or misuse of benzodiazepines and opioids in combination increased significantly from 2000 to 2014. Benzodiazepine abuse or misuse far exceeded cases of opioid abuse or misuse. Death was greater with co-abuse or misuse of benzodiazepines and opioids. Population-level campaigns to inform the public about the risk of death with co-abuse or misuse of benzodiazepines and opioids are urgently needed to address this overdose epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“…Furthermore, recent findingsfocusing largely on acute as opposed to chronic benzodiazepine and opioid exposures-have suggested that fatalities associated with pure benzodiazepine overdose are rare and that the combination of sedative-hypnotic agents with opioids may be an important and understudied factor associated with mortality. 34 We also conducted age-stratified analysis to clarify the burden of psychotropic medications in the elderly, particularly since earlier studies have found that older adults were more likely to receive benzodiazepines and opioids. 2,35,36 Most studies that have identified a positive association between benzodiazepines and all-cause mortality were conducted in predominantly adult or young adult populations, 16,17,20 which makes the mortality risk associated with benzodiazepine use in older adults a poorly understood area.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent findingsfocusing largely on acute as opposed to chronic benzodiazepine and opioid exposures-have suggested that fatalities associated with pure benzodiazepine overdose are rare and that the combination of sedative-hypnotic agents with opioids may be an important and understudied factor associated with mortality. 34 We also conducted age-stratified analysis to clarify the burden of psychotropic medications in the elderly, particularly since earlier studies have found that older adults were more likely to receive benzodiazepines and opioids. 2,35,36 Most studies that have identified a positive association between benzodiazepines and all-cause mortality were conducted in predominantly adult or young adult populations, 16,17,20 which makes the mortality risk associated with benzodiazepine use in older adults a poorly understood area.…”
Section: Discussionmentioning
confidence: 99%
“…The growth in adverse outcomes suggests benzodiazepine prescribing and misuse have increased in tandem, but less is known about benzodiazepine misuse in the U.S. After marijuana use, prescription drug misuse-defined here as use in a manner other than prescribed or by a person to whom it was not prescribed-is the most common type of illicit drug use (13). Most recent benzodiazepine-related work has focused either on misuse in the context of opioid use (14)(15)(16) or tranquilizer and/or sedative medication misuse but not benzodiazepines specifically (17,18). The lack of information about misuse among older adults is particularly striking because they are prescribed benzodiazepines at the highest rates, are most at-risk of related adverse events, and are using alcohol and other substances more than prior cohorts (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Most manuscripts reported on the drug interaction in patients of the abuse and addiction and the ambulatory healthcare settings. For these settings, we were able to conduct pooled analyses of suitable data from 10 studies to provide a quantification of the increased risk for mortality (11,12,18,22,28,29,33,34,36,37). These analyses indicated a significant effect of combined opioid benzodiazepine use on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 13 manuscripts that reported on abuse or intentional misuse of opioids and sedatives, mostly benzodiazepines, were included in this review (see Table 1) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Besides the interaction between opioids and benzodiazepines, interactions between opioids and other centrally acting substances, such as cocaine, antidepressants and alcohol were also commonly reported (12,13,(15)(16)(17)(18)20,23).…”
Section: Abuse and Addictionmentioning
confidence: 99%
See 1 more Smart Citation